Diameter Substrat dan Jenis Lamun di Pesisir Bahoi Minahasa Utara: Sebuah Analisis Korelasi - Alpinina Yunitha; Yusli Wardiatno; Fredinan Yulianda (Jurnal Ilmu Pertanian Indonesia, 2014)
Substrate has an important role for growing and surviving of seagrass as a medium of life and as a supplier of nutrients. Lack of attention towards seagrass is because of less information related to the seagrass ecology itself. The aim of this study is to determine the influence of substrate diameter with it’s density. The study was conducted in April in Bahoi coastal, North Minahasa District, North Sulawesi. This study measured water quality, substrate sampling were taken in the field. The result showed that 6 seagrass species: Enhalus acoroides, Thalassia hemprichii, Halodule uninervis, Cymodecea rotundata, Syringodium isoetifolium, Halpohila ovalis, with good water quality and sand substrate types. This coastal area was dominated by small-sized seagrass. The highest density was found at station B with seagrass type was S. isoetifolium and lowest was at station C with E. acoroides and Sand substrate which had big diameter, type T. hemprichii had high density.